DETERMINAN PERMINTAAN AIR BERSIH DI KOTA SABANG - Imama Imama; Sartiyah Sartiyah; Asri Diana; Fitrah Afandi ZT (Fakultas Ekonomi dan Bisnis UNSYIAH, 2022)
Abstract This study aims to determine the Clean Water Demand in PDAM Tirta Aneuk Laot Sabang. This research was conducted in a period of one year is 2021. This study used multiple linear regression analysis. Partial test using t-test and tests simultaneously using F-test. It also performed classical assumption, that all of these tests using a tool SPSS 22. The results showed that price amounted to 0,462 which mean is that any increase price by 1 percent will increase demand for clean water for 0,462 percent with assuming the influencing factors do not change (ceteris paribus). Amounted to 0,453 visitors to hotels/restaurants. which mean is that any increase of visitors to hotels/restaurants by 1 percent will increase demand for clean water for 0,453 percent with assuming the influencing factors do not change (ceteris paribus). Unknown value of R Square of 0.382. What this means is that the influence contribution of the independent variable on the dependent variable is equal to 38.2 percent. While the remaining 61,8 percent is influenced by other variables yan is not included in this regression model. While most dominant variable among the variables in this study are variable (X1) the price 0,462 in view of Standardized Coefficients. Keywords: Price, Hotel/restaurant visitors and Water demand